Is criminal profiling a valid forensic technique? Application in portuguese cases of rural arsonists - Ribeiro, Rita Alexandra Brilha (My University, 2019)
Criminal profiling was developed to predict personality patterns, behaviors and demographic characteristics of criminals with crime scenes as a fundamental basis (e.g. Douglas, Ressler, Burgess, & Hartman, 1986). This allows the profiler to understand who committed the crime, when, where and how it was done and what was the underlying motivation (Kocsis, 2006). However, there is still controversy regarding the validity of this technique, which is the aim to clarify in the first article. The validity in criminal profiling is related to whether this forensic technique can accurately predict an unknown criminal characteristics (Montet, 2007).There are three types of validity: content validity, construct validity and criterion validity (eg. American Psychological Association, 2018). Most studies use profilers’ and police officers’ beliefs to test criminal profiling validity, others confuse accuracy with validity and some studies test profilers’ predictive capabilities instead of the technique itself and therefore so far there is no well structured investigation direction regarding this technique. Regarding arson’s criminal profiling, there is also no consensual investigation path concerning arsonists’ characteristics and even less studies on rural arsonists. So far exist three different criminal profiles for rural arson from Australia (Willis, 2005), Portugal (Soeiro, Branco, & Carvalho, 2008) and Spain (Sotoca, González, Fernández, Kessel, Montesinos, & Ruíz, 2013) and none is validated. The second article studies 309 rural arsonists’ cases and through an exploratory and confirmatory analysis shows the existence of three valid typologies for rural arson criminal profiling: Expressive Motivation – Psychiatric/Alcohol Problems, Expressive Motivation – Socially Maladjusted and Instrumental Motivation – Socially Adjusted. Thus, this dissertation is divided in two articles: the first one covers criminal profiling validity through a systematic review, while the second one studies its validity applied on rural arson, using a new validation methodology based on the previous article conclusions.

Os perfis criminais foram desenvolvidos para prever padrões de personalidade, comportamentos e características sociodemográficas de agressores, relevando-se também a cena do crime (e.g. Douglas, Ressler, Burgess, & Hartman, 1986). Assim permite-se que os profilers descubram quem cometeu o crime, quando, onde e como foi feito e qual a motivação subjacente (Kocsis, 2006). Contudo, ainda existem controvérsias quanto à validade desta técnica. Nos perfis, a validade relaciona-se à precisão da técnica a prever as características de agressores desconhecidos (Montet, 2007). Existem três tipos de validade: validade de conteúdo, validade de construto e validade de critério (e.g. American Psychological Association, 2018). A maioria dos estudos utiliza crenças dos profilers e polícias para testar a validade dos perfis, outros confundem exatidão com validade e outros avaliam os profilers em vez da técnica. Não existe, portanto, uma linha de investigação bem estruturada sobre a validade da técnica. Quanto aos perfis do crime de fogo posto, não existe uma linha de investigação consensual que defina os comportamentos dos incendiários e existem ainda menos estudos sobre incendiários rurais. Até o momento existem três perfis sobre incêndiários rurais da Austrália (Willis, 2005), Portugal (Soeiro, Branco, & Carvalho, 2008) e Espanha (Sotoca, González, Fernández, Kessel, Montesinos, & Ruíz, 2013) e nenhum é validado. O segundo artigo estuda uma amostra de 309 incendiários rurais e através de uma análise exploratória e confirmatória demostra a existência de três tipologias válidas: Motivação Expressiva – Problemas Psiquiátricos/Álcool, Motivação Expressiva – Socialmente Desajustado e Motivação Instrumental – Socialmente Ajustado. Assim, esta dissertação divide-se em dois artigos: o primeiro abrange a validade dos perfis através de uma revisão sistemática, enquanto o segundo estuda a sua validade aplicada a incêndios rurais, utilizando uma nova metodologia de validação baseada nas conclusões do artigo anterior.
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz
Keywords: Criminal profiling; Validity; Rural arson; Forensic technique